2020
DOI: 10.1038/s41588-019-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Multitrait analysis of glaucoma identifies new risk loci and enables polygenic prediction of disease susceptibility and progression

Abstract: Multitrait analysis of glaucoma identifies new risk loci and enables polygenic prediction of disease susceptibility and progression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
265
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 226 publications
(288 citation statements)
references
References 60 publications
10
265
0
Order By: Relevance
“…More recently, polygenic scores have been developed that integrate the effects of many common genetic variants on disease risk 2 5 . While the common variants have small individual effects on disease risk, they can cumulatively have large effects—producing, in some individuals, risks equivalent to the strong monogenic variants 6 , 7 . A key question is how monogenic and polygenic risk interact: can disease risk from a monogenic variant that causes major disruption to a specific pathway be meaningfully modified by polygenic risk factors that involve small perturbations to a wide range of cellular pathways?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, polygenic scores have been developed that integrate the effects of many common genetic variants on disease risk 2 5 . While the common variants have small individual effects on disease risk, they can cumulatively have large effects—producing, in some individuals, risks equivalent to the strong monogenic variants 6 , 7 . A key question is how monogenic and polygenic risk interact: can disease risk from a monogenic variant that causes major disruption to a specific pathway be meaningfully modified by polygenic risk factors that involve small perturbations to a wide range of cellular pathways?…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has suggested that common variant background modifies the age of disease onset among carriers of high-risk trinucleotide repeats predisposing to Huntington’s disease, the p.Gln368Ter MYOC variant predisposing to glaucoma, and continuous measures, such as height, body mass index, and cholesterol levels among those with rare monogenic mutations 6 , 8 10 . With respect to common diseases such as cancer, the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) studied a large number of BRCA1/2 monogenic risk variant carriers recruited from cancer genetics clinics, noting a relationship between a polygenic score comprised of genome-wide significant loci and the risk of breast, ovarian, and prostate cancer 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the rs10483727 variant in the SIX1 region was significantly associated with POAG diagnosis and progression in a quantitative trait GWA study 4 and with risk of POAG in a later case-control GWA study 3 . More importantly, the rs10483727 variant was associated with POAG across different ethnicities 2 , 5 8 . However, to date, no causal variants driving its association with POAG have been identified.…”
Section: Introductionmentioning
confidence: 94%
“…It can be difficult for DL, and humans, to classify glaucoma in the eyes with less severe disease manifestations or multiple comorbid eye conditions, especially high myopia ( Li et al, 2018 ; Masumoto et al, 2018a ), which requires a larger image database. Furthermore, in order to develop a more dependable screening method, other clinical parameters, including IOP, central corneal thickness and glaucoma genetic informativity biomarkers ( Craig et al, 2020 ) should be integrated. Finally, the application and validation of these advanced methods in a real-world screening setting need additional investigations to bolster its support.…”
Section: Digital Innovations For Eye Diseasesmentioning
confidence: 99%